35.KNOWLEDGE, ATTITUDES, AND PRACTICES (KAP) ON THE PREVENTION OF HEPATITIS B VIRUS TRANSMISSION AMONG HEALTH SCIENCE STUDENTS AT PHENIKAA UNIVERSITY IN 2024 AND RELATED FACTORS (Vietnam Journal of Community Medicine, 2025)
Objective: This study aims to assess the knowledge, attitudes, and practices regarding the prevention of hepatitis B virus transmission among health science students at Phenikaa University in 2024, as well as related factors.Methods: A cross-sectional study was conducted on 223 health science students at Phenikaa University. Data was collected using a self-administered questionnaire, which included general information and items assessing knowledge, attitudes, and practices related to hepatitis B virus transmission prevention.Results: The proportions of students demonstrating adequate knowledge, positive attitudes, and appropriate practices were 92.8%, 69.1%, and 88.3%, respectively. There was a statistically significant relationship between knowledge and attitudes with practice (p
Keywords: hepatitis B; health students; infection prevention; related factors.